The contribution of active Galactic nuclei to the diffuse gamma-ray background - Johnson, P. A.; Mastichiadis, A.; Protheroe, R. J.; Stanev, T. S.; Szabo, A. P. (Journal of Physics G Nuclear Physics, 1994)
We consider the emission of high energy to very high energy $γ$-rays in radio-quiet active galactic nuclei (AGN) or the central regions of radio-loud AGN. We use our results to estimate the $γ$-ray flux from the central regions of nearby AGN, and then to calculate the contribution to the diffuse $γ$-ray flux from unresolved AGN.
Keywords: Astrophysics